2020
DOI: 10.18632/aging.103985
|View full text |Cite|
|
Sign up to set email alerts
|

CD36 upregulates DEK transcription and promotes cell migration and invasion via GSK-3β/β-catenin-mediated epithelial-to-mesenchymal transition in gastric cancer

Abstract: Evidence indicates that the lipid scavenger receptor CD36 has pro-metastatic functions in several cancers. Although CD36 expression correlates with an unfavorable prognosis in gastric cancer (GC), its specific contribution to disease onset, progression, and/or metastasis remains unclear. Using bioinformatics analyses, we ascertained that CD36 expression was increased in metastatic GC specimens in The Cancer Genome Atlas and Gene Expression Omnibus databases and correlated with poor prognosis. In addition, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 30 publications
1
24
0
Order By: Relevance
“…In addition, the expression of CD36 was significantly associated with current predictors for the efficacy of ICIs. The practical application value of CD36 is disease specific [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression of CD36 was significantly associated with current predictors for the efficacy of ICIs. The practical application value of CD36 is disease specific [31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…CD36, a fatty acid translocase, is critical for the regulation of lipid metabolism in GC cells 22,23,68 . Overexpression of CD36 results in elevated fatty acid uptake and could be a confirmatory marker for EMT to a more aggressive phenotype in various tumors, 69–71 including GC 21 . Although APOC2 has been reported to interact with CD36 and initiate downstream signaling in diseases, 11,24 the collaboration between APOC2 and CD36 needs to be further confirmed in GC.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 , 68 Overexpression of CD36 results in elevated fatty acid uptake and could be a confirmatory marker for EMT to a more aggressive phenotype in various tumors, 69 , 70 , 71 including GC. 21 Although APOC2 has been reported to interact with CD36 and initiate downstream signaling in diseases, 11 , 24 the collaboration between APOC2 and CD36 needs to be further confirmed in GC. Our data demonstrated that both CD36 and APOC2 were indispensable for GC migration, invasion, and proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations